Coverage of issues of national identification in the period of Russian empire and Soviet Soviet authority in the Kazakhstani press (Herald of Journalism, 2023)
The article focuses on the reflection in Kazakh publications of the problems of national identification and identity during the period of Russian empire and Soviet Soviet authority. The author seeks to comprehend the national significance of the problems involved in the context of world experience.  During the periods covered in the article, the Kazakh people experienced the most terrible tragedies. So, in the XVIII-XIX centuries, Russian empire pursued a colonial policy on the Kazakh land. The article clarifies that the Soviet government continued the policy of Russian empire in the land issue.  The truth in the Soviet historical textbooks and literature was not told. Kazakh journalism under the influence of Soviet ideology was also powerless.  The demands of independence necessitated the assessment of the reality of national identification and identity in national journalism.  The goal set by the author is to identify the development and formation of Kazakh journalism, to reveal in republican publications the principles and methods, forms of covering issues of national interests.  The research idea of the article takes a step towards a comprehensive solution of the problems of national identification and identity in the republican press. This determines the scientific novelty of the article.  The results of the work are concretized in the course of understanding the materials published in the press as part of the Kazakh people's desire for national identification and identity within the framework of the formation and development of consciousness at the stages of the Russian Empire and Soviet authority.  The article uses the methodology of genesis and typological analysis, comparative study of historical data.  The materials of the article can be used in the preparation of general and special courses in journalism, political science and other social disciplines.  This article is an integral part of research on the theory and practice of Kazakh journalism and is included in the research plan of the Khoja Ahmed Yasawi International Kazakh-Turkish University.  Keywords: tragedy of the nation, Russian empire, Soviet authority, Stalinism, communist ideology, December tragedy.